Good Governance and Human Development in Vietnam: Spatial Empirical Evidence - Quang-Thanh, Ngo (International Journal of Economics and Financial Issues, 2017)
The paper explores the impact of good governance’s disaggregated components on human development in Vietnam by building a system of spatial equations and using a unique cross-province dataset. It finds that institutions prove to be a spatial phenomenon in Vietnam. It also finds that the spatial impact of good governance components differentiates across components of human development. That means good governance can be considered as the policy variables through which we can obtain a combination that sustains human development of the country as a whole and targets at spatial difficult areas. Several spill-over effects are found to exist that can guide policies in the future. The paper also finds that governance mostly affects aspects of human development such as political freedoms, and political participatory, while less on traditional components of human development such as income, health and education. This suggests that the government should consider these additional aspects in the process of handling governance to sustain human development. Keywords: Human Development, Good Governance, System of Spatial Equations JEL Classifications: O15, O53, C31